2019
DOI: 10.1007/s10459-019-09882-9
|View full text |Cite
|
Sign up to set email alerts
|

Parenthood does not explain the gender difference in clinical position in academic medicine among Swedish, Dutch and Austrian physicians

Abstract: Studies have continuously shown that fewer women than men achieve leadership positions in academic medicine. In the current study we explored gender differences in clinical position among academic physicians at three university hospitals, each in a different European country. These countries, Sweden, the Netherlands and Austria, differ in terms of gender equality. We analyzed whether the number of children, working hours or publications could explain gender differences in physicians’ clinical position. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 53 publications
(89 reference statements)
0
17
0
Order By: Relevance
“…No studies beyond those identified were revealed by the 17 contacted scholars. Original data were available for 40 studies, described in 42 articles5 15 52–91 (see online supplementary material 1 for an overview of included studies).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…No studies beyond those identified were revealed by the 17 contacted scholars. Original data were available for 40 studies, described in 42 articles5 15 52–91 (see online supplementary material 1 for an overview of included studies).…”
Section: Resultsmentioning
confidence: 99%
“…The majority of studies (n=35) were conducted in the USA, six included Canadian respondents,61 76 information on Canadian programmes,60 77 79 or schools’ leadership,55 one study was conducted across three countries (UAE, Qatar and Singapore),87 one study was conducted across three European countries (Sweden, the Netherlands and Austria),70 one study was conducted across four European countries (Germany, Sweden, Austria and the UK),71 one study in Norway72 and one study in Croatia 80. The earliest study was conducted in 1999,72 and more than 50% of the studies were published in the past 5 years alone.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations